Risk factors for still birth: a hospital based case control study - Lakshmi, Sujatha Thankappan; Thankam, Uma; Jagadhamma, Preetha; Ushakumari, Anuja; Chellamma, Nirmala; Hariharan, Sankar Vaikam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The study of the risk factors contributing to still birth is imperative in our attempts to bring about a decline in the still birth rate. By identifying the risk factors, we can understand the areas where specific interventions may be applied to bring about a reduction in the still birth rate. The aim of the present study was to identify the risk factors for stillbirth among the mothers attending Sri Avittom Thirunal Hospital, Trivandrum Methods: This was a prospective hospital based case control study conducted from March 2014- September 2015. Sample size was calculated as 100 cases and 200 controls. Odds ratios with 95% confidence interval were calculated using multi variate logistic regression. Results: The major risk factors associated with still births were maternal age, socio economic status, and obesity, sleep position during pregnancy, primi parity, hypertension and febrile illness during pregnancy. The risk of still birth was 3 times higher among mothers with hypertension compared to the control group. Although the prevalence of diabetes slightly more in the case group it was not statistically significant. By analyzing all the risk factors in preparing a model 42% of the risk for still birth was contributed by these factors. Conclusions: The modifiable risk factors seen in this study to prevent still births are maternal sleep position during pregnancy, diabetes, hypertension and febrile illness especially urinary tract infection. By better antenatal care we can detect complications like diabetes, hypertension and manage appropriately thereby preventing complications. By screening for urinary tract infections in every trimester morbidity can be reduced.